Dynamic spectrum management in cognitive radio networks - Siddiqui, Mohammad Tahir; Zyoud, Alhareth (IIUM Press, International Islamic University Malaysia, 2017)
Cognitive radios are intelligent device which are envisioned to operate in an environment where the device can communicate and cooperate for improving the overall performance of the network. Due to this there is a need for cooperative algorithms which can realise numerous gains from cooperation while taking into account the costs for cooperation as well as the effect in a cognitive radio network. For this purpose game theory serves as a highly suited mathematical tool for modelling cooperation in wireless networks. The goal of this book is to bring together a diverse of research works in cognitive radio within the mathematical framework of game theory and matching theory. The starting point is to define the cognitive radio network and how game theory can be applied in cognitive radio networks. Autonomous, self-organizing and distributed algorithm are key to the success of future wireless network. In this regards, two novel algorithms are also discussed to solve the problem of cooperation and improve the over network performance. This book provides review of applications of game theory to cognitive radio networks so that reader can be up to date with recent advances. An outline of key research issue and open challenges is presented for reader to pursue its own research.